Coalitions for Landscape Resilience: Institutional Dynamics behind Community-Based Rangeland Management System in North-Western Tanzania - Eilola, S.; Duguma, L.A.; Käyhkö, N.; Minang, Peter A. (MDPI, 2021)
The past few decades have seen a continuing shift of natural resource management paradigm towards multifunctional and multi-actor adaptive management in hope of achieving more resilient landscapes. Recognizing the multitude of institutional actors and their roles as well as dynamics helps to understand communal behaviour, its manifestations in the landscape and resilience under changing socioecological circumstances. We examined institutional actors and their functions and relationships in a long-standing community-based natural resource management system, the ngitili, in north-western part of Tanzania. The aim of the research was to deepen understanding on the role of institutional arrangements and their limitations in supporting resilience of community-based management system. Data was collected through group discussions and interviews in three case study villages and district level, and institutional arrangements were analysed using 4Rs framework and social network analysis. The study shows that the management arrangements have evolved with time and are based on locally negotiated roles and collaboration among bureaucratic and socially embedded village level actors. These local level actors are resource poor, which hinders collaboration and implementation of ngitili management functions. External interventions have temporarily increased management efficiency in the villages but they did not create sustained multi-scale collaboration networks to address external threats to the ngitili resources. The results show that diversified funding sources, technical support and benefit sharing mechanisms are required to incentivize sustainable resource management. For the management system to be more resilient, the existing institutional actors and their ability to adapt should be nurtured by awareness raising, wider stakeholder participation and bridging organizations.